Occurrence ofArcobacter spp. in Brazilian Minas frescal cheese and raw cow milk and its association with microbiological and physicochemical parameters. (March 2020) - Cruzado-Bravo, Melina L.M.; Barancelli, Giovana V.; Dini Andreote, Ana Paula; Saldaña, Erick; Vidal-Veuthey, Boris; Collado, Luis; Contreras-Castillo, Carmen J.
Abstract: Some Arcobacter species are considered emerging food-borne pathogens. However, their prevalence in dairy products is not well known. Therefore, the aim of the current research is to know the occurrence of Arcobacter species in Minas frescal cheese and raw cow milk and its potential association with physicochemical and microbiological parameters. Two hundred and one food samples (cheese, n = 98 and milk, n = 103) collected between 2016 and 2017 in São Paulo State, Brazil, were analyzed. Arcobacter was isolated using an enrichment broth with further filtration over Arcobacter agar. Colonies were characterized by ERIC-PCR, m-PCR and PCR-RFLP and, when was necessary, sequencing of 16S rRNA and rpoB genes were also assessed. Additionally, cheese samples were evaluated in relation to total coliform (TC), thermotolerant coliforms (TtC), coagulase positive staphylococci (CoPS) count and moisture. Raw milk samples were assessed for aerobic mesophilic bacteria count, TC, TtC, Dornic acidity, proteins, fats, lactose, defatted dry extract, total solids and somatic cell counts. The occurrence of Arcobacter was 10.2% (10/98) and 16.5% (17/103) in cheese and milk samples, respectively. All isolates were identified as Arcobacter butzleri . On the other hand, Multiple Factorial Analysis showed correlation between the presence of this species and the cheese moisture, while this pathogen was correlated with high counts of mesophilic microorganisms and TC in raw milk. No other evaluated parameter in cheese (TC, CoPS) and milk (TtC, Dornic acidity, proteins, fats, lactose, defatted dry extract, total solids and somatic cell counts) showed significant correlation. To date, this is the first report on A. butzleri in Minas frescal cheese, therefore its presence in dairy products could be considered a potential public health concern. Highlights: The occurrence of Arcobacter butzleri was 10.2% in Minas frescal cheese and 16.5% in raw cow milk. First report of Arcobacter in Minas frescal cheese in the state of São Paulo, Brazil. High mesophilic bacteria and total coliforms count correlates with presence of A. butzleri, in raw cow milk samples.